Zn, Cu, Mn and Fe Content in Commercial Organic and Non-Organic Vegetables and Meat Foodstuffs of Sikkim and Darjeeling of India (International Journal of Food and Nutritional Sciences, 2022)
Sikkim and Darjeeling Himalayan Regions are famous for organic farming. Vegetables and meats food stuffs are an important source of metals like Cu, Zn, Mn and Fe which have very important biological roles as they participate in many proteins structure and functions. The concentration of these elements in vegetables and meat food samples of Gangtok and Darjeeling were studied using Atomic Absorption Spectrophotometer (AAS). Among the meat samples, concentration of Zn in the Mutton of both Gangtok (61.59 mg/kg) and Darjeeling (56.53 mg/kg) were above maximum permissible limit (MPL) of 50 mg/kg. Beef (58.63 mg/kg) from Darjeeling was also found to be above MPL. Cu in Chicken samples both from Gangtok and Darjeeling regions exceeded the MPL of 1mg/kg. Though there is no MPL set for Mn and Fe for meat samples, it can be referred from the present study that both the leafy vegetables and meat foodstuffs can be good source of Mn and Fe respectively. The results of this study supply valuable information about the metals contents in commercial organic vegetables and conventionally grown vegetables as well as meat foodstuffs commonly available in Gangtok and Darjeeling area. This is the first database of the chemical elements of the organic vegetables and conventionally grown vegetables as well as meat foodstuffs commonly available in Gangtok and Darjeeling Himalayan regions of India.